AB0815 Living with connective tissue disease related interstitial lung disease: Patient experiences of the disease over time. (23rd January 2014) - Mittoo, S.; Saketkoo, L.A.; Swigris, J.; LeSage, D.; Fischer, A.; Frankel, S.
Abstract : Background: Very limited information is available about the patient experience of connective tissue disease-related interstitial lung disease (CTD-ILD), in terms of global effects on functioning in various psychological and social spheres or of the patients' approaches to coping with the disease and secondary problems related to it. Such information from the patients' perspective would be useful in informing clinical practice and in developing patient reported outcome measures. Methods: Data were collected through a focus group interview, involving nine patients. After institutional review board approval a purposeful sample was recruited from a tertiary-referral hospital in Manitoba, Canada. Inclusion criteria involved English speaking adults with a diagnosis of ILD based on at least one of: histology, chest imaging, presence of shortness of breath or cough, restrictive pulmonary physiology and/or impaired DLCO, resting or exertion-related peripheral oxygen desaturation. Patients with pulmonary hypertension or hypersensitivity pneumonitis were excluded. The interview schedule included two questions ("How have you experienced your disease since the diagnosis of ILD?", "How has the disease changed?"), and the moderator used the WHO-100 domains to develop prompts to insure comprehensiveness. Data were analyzed through inductive development of analyst-constructed themes. The thematic structures of two independent analysts were triangulated. Results: Of the 9 participants, 8 were female and 8 were Caucasian. Mean age was 53.56 (SD =16.02); 4 out of 8 were smokers. CTD sub-types were: idiopathic inflammatory myositis, rheumatoid arthritis, scleroderma, and undifferentiated CTD; one had an overlap of scleroderma and lupus. Five were SSc or SSc overlap. Three main themes emerged. 1. Living with Uncertainty in a Marginal Situation. Uncertainty flowed from areas of confusion between patients and physicians related to diagnosis, evaluation, prognosis, and therapeutic plan. Communication seemed to stagnate after diagnosis. Future disease course and origin of current symptoms were not easily delineated. 2. Struggle Over the New Self, maintaining an autonomous voice and resisting social/family pressures to relinquish normal roles. Parenting and grand-parenting roles were especially important to participants. 3.Development of Resilience through Coping Skills. These skills allowed patients to manage their situation and were empowering. Conclusions: This is the first known effort to report patient reported qualify of life related outcomes (patient experience) in this population. These findings hold important implications for physicians related to enhancing and continuing communication, supporting competence and reinforcing empowered coping. Communication protocols might be developed, and advice might be given as to how patients might maintain as many normal roles as possible. Patient developed coping skills might be studied to identify their effectiveness. Disclosure of Interest: S. Mittoo Grant/Research support from: Actelion, L. A. Saketkoo Grant/Research support from: Actelion, United Therapeutics, J. Swigris: None Declared, D. LeSage: None Declared, A. Fischer: None Declared, S. Frankel: None Declared